Supervision, control and maintenance of automated power grid substations by utilizing augmented and mixed reality technologies : doctoral thesis - Antonijević, Miro (M. Antonijević; Fakultet elektrotehnike i računarstva, 2018)
Ever since electrical substations have existed, they have been monitored and controlled by certain automation systems. Today, this task is usually carried out by Supervisory Control and Data Acquisition (SCADA) systems. SCADA systems today usually implement standardized communication protocols, thus using the standardization influence in the industry to connect to many different devices, enhancing their functionality. The most prominent of the standards is the IEC 61850 international standard (International Electrotechnical Commission) which is used in the majority of new electrical substations in the entire world. The most important enhancements the IEC 61850 standard offers are data management, communication engineering and visualization of process automation information in SCADA applications. The most common way of visualizing process automation data is through Human Machine Interface (HMI) screens in substation control centers. This common data visualization approach creates problems with supervision, control and maintenance procedures because it separates automation data from its corresponding equipment, thus slowing down engineers and making their procedures error-prone. New visualization technologies like Augmented reality (AR) and Mixed reality (MR) have recently gone through a steep maturation process and are being perfected and used in many different environments making them very relevant in any field. This thesis presents a novel methodology for visualizing process related SCADA information to enhance and facilitate human-centric activities in power grid substations such as regular equipment maintenance. The methodology is based on utilizing AR and MR visualization techniques along with the advantages of standards-based communication protocols in power grid substations. This research thesis resulted in development of proof of concept AR and MR applications which are used to display SCADA data near corresponding substation equipment demonstrating originality of the research. The applications use many visualization methods such as widgets and 3D models of substation equipment, making them user-friendly. Since displaying SCADA information needs to be executed considering soft real-time restrictions, certain tests were conducted to prove that these restrictions are respected. The main easily applicable product of the research is the development of an entire software system aimed at supporting maintenance procedures in environments such as power grid substations named the RTGo system. The system incorporates AR techniques into maintenance procedures making them faster, easier and less error-prone. Keywords: power grid, automation, SCADA, augmented reality, mixed reality, maintenance, supervision, control.